IPv6+ 5G bearer network slicing technology and application - Zhuangzhuang QIN; Libiao TU; Yin ZANG; Wenyu GUO (Dianxin kexue)
5G bearer network slicing technology is the basis for meeting differentiated QoS assurance needs of 5G services,especially in vertical industry scenarios.Using key IPv6+ technologies with bearer network slice at the network infrastructure layer,the network slice instance layer,and the network slice management layer has been studied.Taking Beijing Unicom as an example,the objective,application scenarios,evolution plans,existing problems and suggestions of the evolution of smart MAN to IPv6+ based bearer network slice were introduced.